Problems associated with the use of ICT as media in teaching of principles of accounts at ordinary level in Buhera central in Mudanda cluster - Katanganda, Betina (Midlands State University, 2018)
This study focused on the problems associated with the use of ICT as teaching media in Principles of Accounts at Ordinary Level in Buhera Central Mudanda Cluster. The study was motivated by the need to improve the need to improve use of ICT as media. The problem was that Principles of Accounts teachers’ were not fully integrating technology as media in teaching at Ordinary Level. The study therefore looked at the uses of technology and challenges faced by teachers in using technology as media. There is a great need for using ICTs as media such as computers, internet and overhead projector in teaching of Principles of Accounts. Despite the importance of computers, few teachers’ are using as ICT media. A critical literature review was done which revealed that Principles of Accounts teachers’ are facing challenges such as lack of training shortage of time, lack of school support and lack of equipment. The accessible population comprises of ten schools and a sample of three schools was chosen purposively. Respondents’ names were chosen by random sampling technique which gave each teacher an equal chance of being chosen. Six Principles of Accounts teachers responded to questionnaires while 3 heads of schools were interviewed. The research study employed descriptive research design because it enabled the researcher to go into the field and collect data using questionnaires and school heads interviews. The research findings revealed that Principles of Accounts teachers are faced with various challenges such as lack of ICT training, insufficient computer equipment, insufficient time, lack of support from the administration and lack of confidence. The Principles of Accounts teachers are expected to benefit from this research through realization of their need for staff training and development. To collect data questionnaires and interviews were used. The study concluded that with adequate training, technologies and time, there is a greater probability that more teachers will use ICTs as media for teaching Principles of Accounts. It is also recommended that the Ministry of Education should make ICT compulsory and reduce the number of loads for Principles of Accounts to increase planning time. Additionally there is also need to give support such as staff development training as a way to increase the use of ICT in teaching Principles of Accounts.